Pengembangan Kompetensi Guru dan Tenaga Kependidikan dalam Peningkatan Kualitas Sumber Daya Sekolah (Studi Kasus di MTs Raudhatul Muttaqien) - Amanulloh, Mochammad Ja’far Amri (Universitas Negeri Malang, 2024)
Abstract This research aims to investigate efforts to develop the management competencies of teachers and educational staff in improving the quality of school resources, focusing on a case study at MTs Raudhatul Muttaqien. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews, participatory observations, and document analysis. Respondents consisted of the principal, teachers, and educational staff. Data analysis was conducted using the techniques of Miles, Huberman, and Saldana, which include: 1) data collection comprising interviews, observations, and document studies; 2) data condensation, the process of selecting interview, observation, and document study data according to their relevance; 3) data presentation conducted after data condensation, followed by the creation of the research report; 4) data verification and conclusion drawing based on research findings. The research results indicate that the development of teacher and educational staff competencies plays a crucial role in improving the quality of school resources at MTs Raudhatul Muttaqien. Factors influencing the effectiveness of competency development include leadership support, structured training programs, staff collaboration, and active involvement in decision-making. These findings provide valuable insights for policymakers, education managers, and education practitioners in their efforts to improve the quality of education in secondary schools. Abstrak Penelitian ini bertujuan untuk menginvestigasi upaya pengembangan kompetensi manajemen guru dan tenaga kependidikan dalam meningkatkan kualitas sumber daya sekolah, dengan fokus pada studi kasus di MTs Raudhatul Muttaqien. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen. Responden terdiri dari kepala sekolah, guru, dan tenaga kependidikan. Analisis data dilakukan dengan menggunakan teknik Miles, Huberman, dan Saldana, yaitu: 1) pengumpulan data yang melimputi wawancara, observasi dan studi dokumen; 2) kondensasi data, proses pemilihan data wawancara observasi dan studi dokumen sesuai dengan peruntuknya; 3) penyajian data dilakukan setelah kondesasi data selesai, kemudian dibuat laporan hasil penelitian; 4) verifikasi data dan menarik kesimpulan bedasarkan hasil temuan penelitian. Hasil penelitian menunjukkan bahwa pengembangan kompetensi guru dan tenaga kependidikan memainkan peran penting dalam meningkatkan kualitas sumber daya sekolah di MTs Raudhatul Muttaqien. Faktor-faktor yang mempengaruhi efektivitas pengembangan kompetensi meliputi dukungan kepemimpinan, program pelatihan yang terstruktur, kolaborasi antar staf, dan keterlibatan aktif dalam pengambilan keputusan. Temuan ini memberikan wawasan yang berharga bagi pembuat kebijakan, manajer pendidikan, dan praktisi pendidikan dalam upaya meningkatkan kualitas pendidikan di sekolah menengah.